Kajian Spasial Temporal Kemiskinan Di Provinsi Jawa Tengah: Kajian Spasial Temporal Kemiskinan Di Provinsi Jawa Tengah - Sari, Yuria (LPPM UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2024)
Various approaches are taken to examine how poverty grows and develops, accompanied by the search for solutions and appropriate strategies to overcome it. Poverty in a spatial perspective can provide a picture of how the condition of the region where people live can be a cause and effect of the existence of poverty. This research was conducted in Central Java Province with the unit of analysis at the district/city level at three points, namely 2012, 2017, and 2022. The analysis used is the Moran Index and Local Indicator of Spatial Autocorrelation (LISA). The results found that poverty in Central Java Province based on the Moran Index analysis, the value of I in 2012, 2017, and 2022 was 0.258, 0.303, and 0.229, respectively. The Index value at the three points of the year is positive, so it is concluded that the relationship forms a clustered pattern even though the strength of the relationship is quite weak. Then the results at three points of the year show similarities, namely that six districts are poverty hotspots in Central Java based on data on the percentage of poor people. These six regencies include Cilacap, Banyumas, Purbalingga, Banjarnegara, Kebumen, and Purworejo. This means that poverty in all of these areas is high, and so is the surrounding areas.